2009
DOI: 10.2174/1874288200802010100
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Mineral Supplementation Decreases Pain in Rheumatoid Arthritis Patients: A Pilot Study

Abstract: Abstract:The aim of this pilot study was to investigate the efficacy of an alkaline mineral supplement as a means of suppressing disease activity in rheumatoid arthritis (RA) patients, and to check whether any change occurs in the circulating beta-endorphin concentration. Thirty-seven patients with moderately active RA of at least two years duration, who were receiving stable pharmacological treatment, participated in a 12-week study. All patients were randomly allocated to a supplemented group (30g of an alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
4
0
3
Order By: Relevance
“…3 Wu et al (2007) determined that even a minor alteration in extracellular pH may have significant impact on metabolism and the biosynthetic ability of chondrocytes with a maximum glycosaminoglycan synthesis occurring at a pH of 7.2. 115 Research studies have shown that chronic low back pain, 116 rheumatoid arthritis 117 and osteoarthritis of the hands 3 respond favorably to alkaline mineral supplementation (discussed below).…”
Section: Potential Clinical Consequences Of Cssmamentioning
confidence: 99%
See 1 more Smart Citation
“…3 Wu et al (2007) determined that even a minor alteration in extracellular pH may have significant impact on metabolism and the biosynthetic ability of chondrocytes with a maximum glycosaminoglycan synthesis occurring at a pH of 7.2. 115 Research studies have shown that chronic low back pain, 116 rheumatoid arthritis 117 and osteoarthritis of the hands 3 respond favorably to alkaline mineral supplementation (discussed below).…”
Section: Potential Clinical Consequences Of Cssmamentioning
confidence: 99%
“…Studies addressing CSSMA and its consequences through supplementation generally apply one or a combination of alkalizing minerals as interventions (see supplementary data – Table 5). The most frequently applied alkaline minerals in the clinical trials include bicarbonate and the citrate salts: Potassium citrate 3,11,3840,88,116,117,142,143 Potassium bicarbonate 3,7,10,41,43 Sodium bicarbonate 10,76,77,116,117,126,129,144,145 Calcium citrate 3,116,117 Magnesium citrate 3,116,117 Other citrate salts 116,117 …”
Section: Clinical Interventions To Address Cssmamentioning
confidence: 99%
“…In Zusammenarbeit mit Kollegen von der Universität Budapest führten wir an einer dortigen spezialisierten Rheumaklinik eine Untersuchung zur Wirksamkeit eines Basenpräparats bei Patienten mit chronischer rheumatoider Arthritis durch. Die Ergebnisse zeigten, dass die Einnahme des Basenpräparats eine erhebliche Verminderung der Schmerzprobleme mit sich brachte [16]. Die Lebensqualität der Patienten verbesserte sich -gegenüber Patienten der Kontrollgruppe ohne Supplementierung -wesentlich und auch die Einnahme von schmerz-und entzündungshemmenden Medikamenten konnte durch die Basentherapie reduziert werden.…”
Section: Säureempfindliche Natriumkanäleunclassified
“…Studien zeigen, dass bei rheumatoider Arthritis die Entzündung und die Schmerzen umso intensiver sind, je saurer die Gelenkfl üssigkeit ist [7]. Andere Untersuchungen belegen im Gegenzug, dass durch die Nahrungsergänzung mit basischen Citraten die Schmerzsymptomatik bei chronischen Rückenschmerzen [8] und bei rheumatoider Arthritis [9] deutlich gelindert werden kann. [22].…”
Section: Die Chronische Niedriggradige Metabolische Azidose Macht Krankunclassified